Healthy Eating: No-Cook Recipes - Jennifer Hillan; Emily Minton (EDIS, 2011)
Try these quick, easy recipes for balanced, healthy meals. No cooking required! This revised 1-page fact sheet was written by Jennifer Hillan and Emily Minton and published by the UF Department of Family Youth and Community Sciences, May 2011.